Estrategia psicoeducativa basada en las competencias emocionales para prevenir el consumo de alcohol en los adolescentes del décimo año paralelo a, del colegio de bachillerato 27 de Febrero, 2018-2019. - Arizaga Ordoñez, Rosa Fernanda (2019)
The alcohol consumption in adolescents causes physical, phychological, social, emotional and school damage; that hinder the integral development, with risk of dependency later. Therefore, an investigation was carried out called: PSYCHOEDUCATIONAL STRATEGY BASED ON EMOTIONAL SKILLS TO PREVENT ALCOHOL CONSUMPTION IN ADOLESCENTS, BEING APPLIED WITH THE TENTH YEAR PARALLEL A, OF THE FEBRUARY 27 HIGH SCHOOL, 2018-2019.; the objective was to implement a psychoeducational strategy based on emotional competencies to prevent alcohol consumption in the investigated adolescents. It was a descriptive study, with a cross-sectional and experimental design; the methods used were: scientific, analytical-synthetic, deductiveinductive and the statistic of the Pearson linear correlation coefficient (r). The Intention and Attitudes Scale to alcohol consumption was applied in a sample of 23 students between 14 and 17 years old. The found results were (pre-test), the 78.26% of those investigated showed positive attitudes towards alcohol consumption (greater intention); after the application of the proposal (post-test), significant achievements evidenced that 82.61% externalize negative attitudes towards alcohol consumption (less intention). The validation’s results of the strategy reached a value of r (x; y) = 0.70, which means a high positive correlation. This concluded that most of the adolescents investigated have positive attitudes towards consumption; After the application of the psychoeducational strategy, the students present high percentages of negative attitudes, the application of the proposal is validated because the emotional competences trained in the workshops do allow a change of favorable attitudes for the prevention of alcohol consumption, so it is recommended that DECE apply the psychoeducational strategy to all students of the institution, and include parents and teachers with the purpose of achieving student welfare and a life without alcohol.